Genome Sequence of the Melanin-Producing Extremophile Aeromonas salmonicida subsp. pectinolytica Strain 34melT - Pavan, María Elisa (2013)
The genome of Aeromonas salmonicida subsp. pectinolytica strain 34melT, isolated from a heavily polluted river, contains several genomic islands and putative virulence genes. The identification of genes involved in resistance to different kinds of stress sheds light on the mechanisms used by this strain to thrive in an extreme environment.